Making public politics private: A narrative study of apartheid racial ideology and its effects on white teenage female sexual desire in post-apartheid South Africa - Botsis, Hannah (School of Education, 2014)
An effect of apartheid among the youth has been that transformation in educational institutions has largely not moved beyond artificial interaction. There is an obvious divide between public rhetoric of integration and private experience. A reason for this may be that the private realm is a fertile and productive space for the reproduction of prejudice, where desire is seemingly coded in private tastes and not political ideologies. Theoretically I examine how historical public discourses come to function as personal norms, expressed as personal desire not political ideology. Literature has shown that these racial ideologies function both to fetishize the Other in interracial relationships and to maintain the hegemony of whiteness in interracial contact. Through narrative interviews with a select group of white teenage girls from a mixture of schools in the Northern Suburbs of Cape Town, I analyse how historical power relations become an intimate part of our subject experience. Drawing on a psychoanalytical account of ideology I examine how their racial subjectivities are predicated on exclusionary logics that bar certain objects from being produced as desirable for them.